2011
DOI: 10.1007/s11427-011-4254-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in phosphorus acquisition from sparingly soluble P sources is related to root morphology and root exudates in Brassica napus

Abstract: Genotypic variations in the adaptive response to low-phosphorus (P) stress and P-uptake efficiency have been widely reported in many crops. We conducted a pot experiment to evaluate the P-acquisition ability of two rapeseed (Brassica napus) genotypes supplied with two sparingly soluble sources of P, Al-P and Fe-P. Then, the root morphology, proton concentrations, and carboxylate content were investigated in a solution experiment to examine the genotypic difference in P-acquisition efficiency. Both genotypes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…A connection between enhanced root surface area and grain yield under low-P conditions in the soil was also found for Sb03g031680, where the A allele at SNP 1541 jointly increased both traits in the SAPst. Indeed, P deficiency has been shown to enhance root growth, leading to significant increases in root length and root surface area in Cucumis melo (Fita et al, 2011) and Brassica napus (Zhang et al, 2011). The hypothesis that Sb03g031680 and Sb03g031690 control root morphology, as was the case for OsPSTOL1 in rice (Gamuyao et al, 2012), is reinforced by the presence of highly significant QTLs related to root morphology traits at approximately 12 Mb from the PSTOL1 homologs at position 60 Mb on chromosome 3.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A connection between enhanced root surface area and grain yield under low-P conditions in the soil was also found for Sb03g031680, where the A allele at SNP 1541 jointly increased both traits in the SAPst. Indeed, P deficiency has been shown to enhance root growth, leading to significant increases in root length and root surface area in Cucumis melo (Fita et al, 2011) and Brassica napus (Zhang et al, 2011). The hypothesis that Sb03g031680 and Sb03g031690 control root morphology, as was the case for OsPSTOL1 in rice (Gamuyao et al, 2012), is reinforced by the presence of highly significant QTLs related to root morphology traits at approximately 12 Mb from the PSTOL1 homologs at position 60 Mb on chromosome 3.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, increased root surface area is achieved by a combination of reduced root diameter and enhanced elongation of relatively thinner roots (Fitter et al, 2002). There is both intraspecific and interspecific genetic variation for P deficiency tolerance in crop species (Lynch andBrown, 2001, 2012;Mudge et al, 2002;Paszkowski et al, 2002;Rausch and Bucher, 2002;Huang et al, 2011;Zhang et al, 2011;Leiser et al, 2014a) that can be explored to develop P-efficient cultivars.…”
mentioning
confidence: 99%
“…It was found that the amount and composition of OAs in the rhizosphere varied with plant species and P status of growth medium as well as the growth stage of the plant (Lambers et al 2006). P-efficient plant species or cultivars secrete larger amounts of P-mobilizing OAs under LP stress, such as barley (Gahoonia et al 2000), maize (Hinsinger 2001), rape (Brassica napus L.) (Zhang et al 2011) and Arabidopsis (Narang et al 2000), resulting in alleviation of P stress. This observation implied that an LP-tolerant genotype XZ99 had the lowest contents of all three OAs including citrate, succinate and malate under CK conditions, and the highest contents under LP stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, B. napus has high P demand for producing high seed yield and is greatly sensitive to phosphorus deficiency. In the past decade, several studies reported that significant genotypic difference exists in P acquisition and seed mineral accumulation among B. napus cultivars [4][5][6], suggesting that it is an available pathway to develop P-efficient B. napus cultivars further.…”
Section: Introductionmentioning
confidence: 99%